Inhibiting the “isolated island” effect in simulated bone defect repair using a hollow structural scaffold design - Liu, Xiao; Gao, Jianpeng; Liu, Jianheng; Zhang, Licheng; Li, Ming (Frontiers in Bioengineering and Biotechnology, 2024)
The treatment of bone tissue defects remains a complicated clinical challenge. Recently, the bone tissue engineering (BTE) technology has become an important therapeutic approach for bone defect repair. Researchers have improved the scaffolds, cells, and bioactive factors used in BTE through various existing bone repair material preparation strategies. However, due to insufficient vascularization, inadequate degradation, and fibrous wrapping, most BTE scaffolds impede new bone ingrowth and the reconstruction of grid-like connections in the middle and late stages of bone repair. These non-degradable scaffolds become isolated and disordered like independent “isolated islands”, which leads to the failure of osteogenesis. Consequently, we hypothesized that the "island effect" prevents successful bone repair. Accordingly, we proposed a new concept of scaffold modification — osteogenesis requires a bone temporary shelter (also referred to as the empty shell osteogenesis concept). Based on this concept, we consider that designing hollow structural scaffolds is the key to mitigating the “isolated island” effect and enabling optimal bone regeneration and reconstruction.